The potential of Nigella Sativa and thymoquinone in salvaging the embryo from effects of toxic paternal exposure - Abdul Samat, Nadia Hanis; Abdul Rahman, Suzanah; Ahmad, Nur Amalina; Abdullah, 'Afif Raihan; Mohamad Zahri, Syazana (2016)
Studies have reported that exposure to cyclophosphamide (CPA) for cancer treatment result in adverse reproductive consequences. Over-production of reactive oxygen species causes oxidative stress thus affecting the DNA in male germ cell inducing sperm defects. Our goal is to assess the potential effects of Nigella sativa extract (NSE) and thymoquinone (TQ) on sperm and embryo quality following fertlization from sperm produced from germ cells which have been exposed to the damaging alkylating effects of CPA. Thirty male ICR mice were divided into six groups; (I) Group 1: Vehicle-treated control (normal saline), (II)Group 2: CPA-only, (III)Group 3: TQ-only, (IV)Group 4: NSE-only, (V) Group 5: CPA followed by TQ and (VI)Group 6: CPA followed by NSE. Treatment was given to the mice based on the grouping for 32 days where the dosage for CPA is 200mg/kg and for NSE and TQ at 10mg/kg. Groups (V) and (VI) were treated with CPA followed by NSE and TQ after six hours. Animals were sacrificed at 33 days by cervical dislocation and sperm from caudal epidydymis were taken for analysis and in vitro fertilization (IVF) with eggs from untreated female. Fertilization rates and embryo development were assessed and monitored for 5 days. TQ and NSE supplementation to CPA-exposed male mice have no significant effect (p>0.05) on the total number of sperm if compared to CPA-only exposed mice. NSE and TQ supplementation has been shown to have significant effect (p<0.05) on the percentage of motile sperm as well as the number of abnormal sperm. There are four types of abnormalities of the sperm were found which includes folded sperm, amorphous, banana-like and lastly the head lack of usual hook. Finally, the embryo quality based on embryo scoring by Baczkowski (2004), shows a significant improvement by the supplementation of TQ and NSE to CPA-exposed male mice (p<0.05). Overall, both NSE and TQ have indicated chemopreventive potential against the cytotoxicity of cyclophosphamide on the reproductive capacity and fertility.